PP.13.22: TNF-ALPHA MEDIATES SIGNALING PATHWAYS OF OXIDATIVE STRESS INDUCED BY ETHANOL CONSUMPTION. (June 2015) - Simplicio, J.; Cunha, T.M.; Tirapelli, C.R.
Abstract : Objective: The aim of this study was to evaluate the role of TNF-alpha in the induction of oxidative stress caused by chronic ethanol consumption and the involvement of PVAT in such response. Design and method: Wild type (WT) C57/BL6 and knockout mice for TNFR1receptors (TNFR1-/-) were treated with ethanol 20% (v/v) for 9 weeks. The thoracic aorta was used in the following biochemical experiments: detection of superoxide anion (O2-); determination of thiobarbituric acid reactive species (TBARS) and 8-isoprostane; evaluation of nitrate, cytokines, catalase activity and GSH levels (Ethical committee:12.1.1654.53.9). Results: In WT mice, ethanol treatment increased the levels of cytokines (TNF-alpha, IL-6, IL-1beta and IL-18) in the aorta with PVAT. Treatment with ethanol increased O2- levels (RLU/mg protein) in aortas with PVAT from WT mice (Control: 149 ± 8, n = 5; Ethanol: 235 ± 13, n = 5). This increase was not observed in aortas from TNFR1-/- mice. Ethanol treatment increased plasma TBARS levels (nmol /ml) (Control: 16.2 ± 1.5, n = 7; Ethanol 23.9 ± 1.7, n = 6) in WT mice. In WT mice, ethanol increased the levels of TBARS (nmol/mg protein) in aortas without PVAT (Control: 12.1 ± 0.8, n = 5; Ethanol: 18.6 ± 2.0, n = 6) and with PVAT (Control: 9.5 ± 0.8, n = 5; Ethanol: 16.9 ± 2.5, n = 5). This increase was not observed in aortas and plasma from TNFR1-/- mice. Furthermore, 8-isoprostane levels were reduced in TNFR1-/- animals treated with ethanol compared to others groups. In WT mice, the levels of nitrate/nitrite (mmol/mg protein) were reduced in the aorta without PVAT (Control: 16.6 ± 1.6, n = 5; Ethanol: 7.7 ± 0.8, n = 6) and with PVAT (Control: 15.0 ± 3.5, n = 5; Ethanol: 1.9 ± 0.3, n = 5). This increase was not observed in aortas from TNFR1-/- mice. WT showed reduced catalase activity in aorta without PVAT, but not TNFR1-/- mice after treatment with ethanol. GSH levels were higher in aorta with PVAT than aorta without PVAT in both groups. Conclusions: TNF-alpha modulates vascular oxidative stress induced by chronic ethanol consumption and is supposed to PVAT does not display a beneficial/protective action in reducing the vascular inflammation and oxidative damage caused by ethanol.